2015
DOI: 10.1016/j.ijgo.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of the PRECEDE model to improve sexual function among women with hysterectomy

Abstract: The findings confirm the effectiveness of an educational program based on the PRECEDE model in terms of improving sexual function among women with hysterectomy. Iranian Registry of Clinical Trials: IRCT2014122220401N1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
2
8
0
4
Order By: Relevance
“…Based on their findings, this model significantly increased the female sexual function and their 6 sub-scales in the intervention group. The findings of this study are in good agreement with the results of our study as well (37).…”
Section: Discussionsupporting
confidence: 93%
“…Based on their findings, this model significantly increased the female sexual function and their 6 sub-scales in the intervention group. The findings of this study are in good agreement with the results of our study as well (37).…”
Section: Discussionsupporting
confidence: 93%
“…But in the second phase (after training), the mean score of the reinforcing factor increased and was significant between intervention and control groups (P<0.05). In the study by Hosseini et al on the use of the PRECEDE model to improve sexual performance in women with hysterectomy, it was shown that reinforcing and behavior variables in the control group significantly increased after training (P<0.05) [22]. Their findings are consistent with the findings of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Sexually inactive women in last four week were not included. This sample size reached to one hundred seventy six(176) women as eight (8) women were lost at the time of the follow up as for a cultural issues and shame.…”
Section: Sample Size Type and Techniquementioning
confidence: 99%
“…The questionnaire evaluated 20 items in three domains: predisposing factors (13 items), enabling factors (4 items), and reinforcing factors (3 items). In the domain of predisposing factors, knowledge (6 items) was evaluated on the basis of yes/no/don't know questions (possible score 6-18), and attitudes, beliefs, and values (7 items) were evaluated using a three-point Likert scale (from agree = 3, uncertain = 2, and disagree = 1, possible score (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The researcher considers negative attitude if total score was less than 14 while, positive attitude, if the total score more than 14.…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation